Numerical Study of the Influence of Tube Arrangement on the Flow Distribution Inside the Heat Exchanger in the PCCS - Zhou, Jian; Yue, Yanwei; Meng, Zhaoming; Sun, Zhongning (Frontiers in Energy Research, 2020)
Passive containment cooling system (PCCS) is widely applied in a new generation of nuclear power plants. The initial heat exchanger is the most improtant heat transfer device in the PCCS. Past studies show that the flow distribution has a great influence on the heat transfer performance of a heat exchanger. And a lot of work has been done on improving the flow distribution uniformity of the heat exchanger such as the geometry modification, proper choice of the geometry parameters. However, little work has been done on the tube arrangement. For a heat exchanger applied in the industry, the number of tubes are huge, and it is unrealistic to arrange all the tubes in a row on the one side of the heat exchanger. Therefore, more work should be paid on the influence of the tube arrangement on the flow distribution in the heat exchanger. The present study numerically investigated the effect of the tube arrangement on the flow distribution in a Central-type parallel heat exchanger. Six different kinds of tube arrangement have been investigated on the flow distribution and the pressure loss characteristics of the heat exchanger. The obtained results show that the tube arrangement has a great influence on the flow distribution and the staggered tube arrangement provides a better flow distribution than the aligned tube arrangement.